2013
DOI: 10.1177/0194599812459636
|View full text |Cite
|
Sign up to set email alerts
|

Panel 5: Microbiology and Immunology Panel

Abstract: Objective The objective is to perform a comprehensive review of the literature from January 2007 through June 2011 on the virology, bacteriology, and immunology related to otitis media. Data Sources PubMed database of the National Library of Medicine. Review Methods Three subpanels with co-chairs comprising experts in the virology, bacteriology, and immunology of otitis media were formed. Each of the panels reviewed the literature in their respective fields and wrote draft reviews. The reviews were shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 275 publications
(517 reference statements)
0
6
0
Order By: Relevance
“…Viral upper respiratory tract infections often precede or coincide with episodes of AOM; examples include respiratory syncytial virus, adenovirus, and cytomegalovirus 27. Viral infections are now thought to have a pivotal role in AOM progression, and recent randomized controlled trials have demonstrated the role of antiviral treatment for AOM 28.…”
Section: Etiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Viral upper respiratory tract infections often precede or coincide with episodes of AOM; examples include respiratory syncytial virus, adenovirus, and cytomegalovirus 27. Viral infections are now thought to have a pivotal role in AOM progression, and recent randomized controlled trials have demonstrated the role of antiviral treatment for AOM 28.…”
Section: Etiologymentioning
confidence: 99%
“… 25 , 26 Viral upper respiratory tract infections often precede or coincide with episodes of AOM; examples include respiratory syncytial virus, adenovirus, and cytomegalovirus. 27 Viral infections are now thought to have a pivotal role in AOM progression, and recent randomized controlled trials have demonstrated the role of antiviral treatment for AOM. 28 It is thought that viral infection of the nasopharynx creates an environment that promotes bacterial colonization, adhesion to cells, and invasion of the middle ear.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Because OM causes hearing loss during a crucial period for speech and language development, children with frequent middle ear infections may suffer speech and language disabilities (1)(2)(3). Streptococcus pneumoniae is a major Gram-positive bacterium causing OM (2,8,9). Current S. pneumoniae vaccines have a limited impact on OM, and inappropriate antibiotic use increased antibiotic resistance (9)(10)(11)(12).…”
mentioning
confidence: 99%